(untitled) (JBIOEDRA: Jurnal Pendidikan Biologi, 2025)
Angiosperms are flowering plants whose seeds are enclosed within carpels or fruit structures, and they represent the most abundant and widely distributed group of plants on Earth. Angiosperms play an important role in maintaining ecosystem stability and serve as essential resources for education, ecology, and conservation studies. This study aimed to identify and document the diversity of angiosperm species in the Integrated Laboratory Park of UNIPMA as a potential learning resource for biology education. The research was conducted in October 2025 using an exploratory method combined with direct field observation and in situ plant identification. Data collection involved systematic exploration of the study area and identification of plant species based on morphological characteristics. The results of the study revealed a total of 20 angiosperm species belonging to various families. The relatively high diversity of angiosperms indicates that the environmental conditions of the Integrated Laboratory Park, such as soil quality, light availability, and microclimate, are highly supportive of plant growth and species richness. The findings of this study can serve as a scientific reference for UNIPMA students in recognizing, understanding, and utilizing angiosperm diversity within the campus environment, as well as supporting practical activities and field-based learning in plant biology courses.